The development of the electric energy management system for series hybrid electric vehicle - Gan, Leong Ming (2008)
Among all the alternative energy and power plant development, Hybrid Electric Vehicle (HEV) is one of the most applicable systems. Similar to conventional vehicle, it still used internal combustion engine as the power source. Nowadays, the integration between IC engine and electric generation system could be found in various technologies. Several problems with HEV still remain unsolved although many researches had been carried out to build HEV. The research constraints include the size of the battery, charging period and the cost of the technology. In nation car market, some car manufacturers are keen to promote HEV to the nation municipal. Miserably, the price of the HEV is high and the popularity is remained low. To improve environment pollution, A-HEV project was carried out by local university level team to design, construct and develop a simple, attachable and low cost HEV system. Since it was the initial step for the research team move forward HEV technology, series HEV concept was referred. To further reduce the complexity and the attractiveness of the vehicle design, buggy platform was selected in this project. As the HEV technology cost is domain by the battery and electric management system, an alternate capability concept with programmable logic control system were adopted in the A-HEV project as well.